Efficient Model of Economic Growth in the Conditions of Post-Crisis Development of the Society in the Republic of Kazakhstan - USKELENOVA, Assel T.; SHADIYEV, Kairatbek K.; TATYGULOV, Aidar A. (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The relevance of the research is conditioned by the issues of measuring the economic growth rates and factors. The paper discusses the models of economic growth – Keynesian, neo-Keynesian, Harrod and Domar model, as well as Solow one that shows how savings, population growth and scientific and technical advance act on the growth of production volumes over time. The paper focuses on questions of the development of national economy of the Republic of Kazakhstan. The leading research approach is factor- and goal-based one that has allowed the authors to determine the challenges to the national economy in the global reality and to give a comprehensive consideration of the economic development path and, respectively, of parameters and factors of change in the life of the society. Factors influencing the economic growth and formation of the ‘knowledge economy’ have been described and crisis phenomena of Kazakhstan economic development path have been revealed. The paper also gives ground for quality change of the country's economic life, its technological foundations and institutions aimed at forming the provision for an innovative model of development of the state. The materials of the paper are of practical use for the real sector economists as well as for the academic staff of educational establishments.